(untitled) (Journal of Oriental Studies, 2019)
Wisdom, outlook and vision of people are reflected in his language, especially in phraseology. The article compares the phraseological units of the Korean language with the Kazakh language using the example of phraseological units from popular Korean serials. Phraseologisms are a “twisted text” that reflects the mentality of a given nation and distinguishes it from another. In this article, researchers revealed the essence and significance of phraseological units of the Korean language and resulted in ways of translating into Kazakh language, revealed features and differences. Key words: TV series, translator, cinema, cinema, poet, linguoculturology, features, translation, etc.